Allium Sativum As Antimalaria Agent Via Falciapin Protease-2 Inhibitor Mechanism : Molecular Docking Perspective - Syaban, Mokhamad Fahmi Rizki; Rachman, Hafidh Alyza; Arrahman, Azmirfani Diti; Hudayana, Nur; Khamid, Jaya Purna; Pratama, Farhan Adi (Universitas Brawijaya, 2021)
Background: Malaria is an endemic disease that can lead to death. Malaria control is a threatening cause of resistance to antimalarial drugs so that renewable therapies are needed to overcome this disease. The chemical compounds of garlic have potential as antimalarial agents, but the mechanism is still unknown. Aim: This research will predict the compounds' molecular mechanism in garlic (Allium sativum) using the in-silico method. Methods: The In-silico method using chemical compounds in Allium sativum were obtained from PubChem, and Falciapain protease-2 was obtained from the Protein Data Bank. Then performed a docking simulation between ligand-protein and analyzed it in 3D. We were used PyRx, Pymol, and DS (Discover Studio) software for analysis and visualization of the interaction of ligand-protein. Results: The results we got, the Alliin compound contained in Allium sativum has the strongest bond with Falcipain protease-2. Allin has fulfilled Lipinski Rule, so Alliin drug-likeness potentially. Alliin has antimalarial activity with its inhibition mechanism against Falcipain protease-2. Conclusion: We recommend this study as a reference for further research on Aliin compounds as antimalarials through in vitro and in vivo methods.